Praktik Sosial Inklusif dalam Pemberdayaan Pekerja Penyandang Disabilitas pada Kafe Inklusi di Kota Bandung - Wahyudi, Trias Ananta; Wilodati, Wilodati; Mujayapura, Muhammad Retsa Rizaldi (Lembaga Teewan Journal Solutions, 2026)
Persons with disabilities continue to face various barriers to equal participation in social life, including employment. Inclusive cafés serve as spaces that provide employment access for workers with disabilities. This study aims to analyze inclusive social practices within the field of inclusive cafés in Bandung City and their contribution to empowering workers with disabilities. The study employed a qualitative approach using a multisite case study method at Café More Wyata Guna, Hagya Coffee and Roastery, and Dali Café. Data were collected from 14 purposively selected informants through non-participant observation, semi-structured interviews, and documentation. The data were thematically analyzed using Nvivo through within-site and cross-site analyses, complemented by source and technique triangulation. The findings indicate that inclusive social practices are shaped by the interplay of habitus, capital, and field. These practices are manifested in meaningful work roles, adaptive task allocation, accessible communication, gradual assistance, and recognition. Such practices contribute to the intrapersonal, interactional, and behavioral components of worker empowerment